Adaptability and stability of peach and nectarine cultivars in subtropical climate - Matias, Rosana Gonçalves Pires; Bruckner, Cláudio Horts; Silva, Danielle Fabíola Pereira da; Carneiro, Pedro Crescêncio Souza; Oliveira, João Alison Alves (Revista Ceres, 2017)
Information on adaptability and stability of fruit production in different environments or years is crucial to increasing agricultural production potential. Therefore, the objective of this study was to evaluate whether there is interaction between cultivars and years, as well as to assess the stability of peach and nectarine cultivars regarding fruit fresh mass, SS/TA ratio, and cycle length in Viçosa –MG, Brazil. The characteristics fruit fresh mass (FM), soluble solids/titratable acidity ratio (SS/TA), and cycle length (CL) were evaluated in 28 cultivars of peach and two cultivars of nectarine from the orchard of the Universidade Federal de Viçosa, in 2011, 2012, and 2013. The methods used to determine the phenotypic stability across time were Eberhart & Russell (1966) and the Traditional. The interaction cultivars x years was significant for all traits. Cultivar ‘Josefina’ showed broad adaptability for SS/TA ratio, and cultivars ‘Flordaprince’ and ‘Tropical’ for cycle length. For favorable environments, the cultivars ‘Capdebosq’ and ‘Maciel’ are indicated regarding the characteristic fruit mass, and ‘Coral’ and ‘Talismã’ for SS/TA ratio. ‘Rubimel’ was adaptable to unfavorable environments regarding fruit mass.